2005
DOI: 10.7589/0090-3558-41.1.126
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Four Serologic Assays in Screening for Brucella Exposure in Hawaiian Monk Seals

Abstract: A survey for Brucella spp. antibodies was undertaken on 164 serum samples from 144 Hawaiian monk seals (Monachus schauinslandi) from the northwestern Hawaiian Islands collected between 1995 and 2002. The buffered antigen plate agglutination test (BPAT), the indirect enzyme immunoassay (I-ELISA), the competitive enzyme immunoassay (C-ELISA), and the fluorescence polarization assay (FPA) were compared with regard to their ability in detecting antibodies to Brucella spp. in the serum samples. Overall, antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…and those to other crossreacting gram-negative bacteria (Nielsen, 1990;Samartino et al, 1999). Whether the cELISA behaves similarly in pinnipeds is unknown, but our study is consistent with findings in Hawaiian monk seals (Monachus schauinslandi), in which it was concluded that the iELISA was an unreliable test for the identification of Brucella antibody-positive individuals (Nielsen et al, 2005). The FPA returned the fewest number of positive results; this is also consistent with Nielsen et al (2005), who suggested that the FPA is significantly more specific than the iELISA and marginally more specific than the cELISA.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…and those to other crossreacting gram-negative bacteria (Nielsen, 1990;Samartino et al, 1999). Whether the cELISA behaves similarly in pinnipeds is unknown, but our study is consistent with findings in Hawaiian monk seals (Monachus schauinslandi), in which it was concluded that the iELISA was an unreliable test for the identification of Brucella antibody-positive individuals (Nielsen et al, 2005). The FPA returned the fewest number of positive results; this is also consistent with Nielsen et al (2005), who suggested that the FPA is significantly more specific than the iELISA and marginally more specific than the cELISA.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, all juvenile and adult female samples plus sera from 10 pups from each year were tested by a second cELISA, an indirect ELISA (iELISA), and a fluorescence polarization assay (FPA) at the Canadian Food Inspection Laboratories (Ottawa, Canada), so that test performance and agreement could be assessed. Although these tests have been used to investigate Brucella antibody status in marine mammals (Nielsen et al, 2005), they have not been validated for this purpose.…”
Section: Antibody Assaysmentioning
confidence: 99%
See 3 more Smart Citations